2022
DOI: 10.1029/2021jd035911
|View full text |Cite
|
Sign up to set email alerts
|

Future Land Precipitation Changes Over the North American Monsoon Region Using CMIP5 and CMIP6 Simulations

Abstract: The North American Monsoon (NAM) dominates the annual cycle of rainfall over the southwest United States and western Mexico, feeding into economic and environmental resources, including agricultural practices, water management, and fire season variability. The peak monsoon season is observed between July through September, with the largest rainfall occurrence over the elevated terrain of the Sierra Madre Occidental (SMO) and accounts for 70%-80% of the mean annual rainfall (Pascale et al., 2019). Variations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
(109 reference statements)
0
7
1
Order By: Relevance
“…Our comprehensive analysis reveals that neither CMIP5 nor CMIP6 model simulations satisfactorily capture all aspects of the temporal and spatial characteristics of the CRU data across the entire ALL region and its two sub-regions. Moreover, most institutions employing CMIP6 showed CRI values that were lower or closer to the reference than those using CMIP5 for both the ALL region and its sub-regions in certain seasons, which is contrary to recent studies that have suggested overall improvements in the precipitation change simulations in CMIP6 models on a global scale [79,80]. Specifically, we observed that most model simulations tend to overestimate the magnitude of mean annual precipitation in the ALL region across all four seasons.…”
Section: Discussioncontrasting
confidence: 99%
“…Our comprehensive analysis reveals that neither CMIP5 nor CMIP6 model simulations satisfactorily capture all aspects of the temporal and spatial characteristics of the CRU data across the entire ALL region and its two sub-regions. Moreover, most institutions employing CMIP6 showed CRI values that were lower or closer to the reference than those using CMIP5 for both the ALL region and its sub-regions in certain seasons, which is contrary to recent studies that have suggested overall improvements in the precipitation change simulations in CMIP6 models on a global scale [79,80]. Specifically, we observed that most model simulations tend to overestimate the magnitude of mean annual precipitation in the ALL region across all four seasons.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, the Taylor diagram was used to compare the capabilities of the CMIP6 models to reproduce monthly precipitation through the standard deviation (STD), the RMSE, and spatial correlation coefficient (SCC) during the validation years (Taylor, 2001). According to these metrics, a skill score was implemented to further evaluate the GCMs' accuracy and select optimal models for reproducing spatio‐temporal distribution of precipitation over the Haihe River Basin (L. Chen & Frauenfeld, 2014; Hernandez & Chen, 2022). The skill score was calculated by the following equation: S=(1+SCC)44SDR+1SDR2 $S=\frac{{(1+\text{SCC})}^{4}}{{4\left(\text{SDR}+\frac{1}{\text{SDR}}\right)}^{2}}$ where SDR is the ratio of STD between the model and observations.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have pointed out that as the side length of the region approaches one hundred kilometers, the impact of this term on precipitation becomes negligible and can be disregarded (Akiyama, 1975; C.‐C. Chen et al., 2019; Hernandez & Chen, 2022; J. Jiang et al., 2020). The last term in Equation depicts the vertical integral moisture flux convergence (MFC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations